2019
DOI: 10.1111/jvim.15438
|View full text |Cite
|
Sign up to set email alerts
|

Use of 2‐dimensional speckle‐tracking echocardiography to assess left ventricular systolic function in dogs with systemic inflammatory response syndrome

Abstract: Background Early identification of systolic dysfunction in dogs with systemic inflammatory response syndrome (SIRS) potentially could improve the outcome and decrease mortality. Objective To compare 2‐dimensional speckle tracking (2D‐STE) with 2‐dimensional (2D) and M‐mode echocardiography in the evaluation of systolic function in SIRS dogs. Animals Seventeen SIRS and 17 healthy dogs. Methods Prospective observational case‐control study. Each dog underwent physical examination, conventional echocardiography, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 67 publications
0
16
0
Order By: Relevance
“…PDA is the most common congenital heart defect in dogs, resulting from the failure of the ductus arteriosus to close, a normal fetal structure that shunts blood from the pulmonary artery to the aorta by bypassing the nonfunctional lung and normally closes soon after birth [56]. After birth, the rise in systemic pressure and the drop in pulmonary artery pressure cause blood to flow through the PDA from the aorta to the pulmonary artery (left-to-right shunt), resulting in pulmonary over circulation and volume overload of the left atrium and LV [56]. A study by Spalla et al compared dogs with PDA with healthy controls and found a significant increase in LV dimensions, indicating LV overload in the PDA groups (Table 3) [47].…”
Section: Patent Ductus Arteriosus (Pda)mentioning
confidence: 99%
“…PDA is the most common congenital heart defect in dogs, resulting from the failure of the ductus arteriosus to close, a normal fetal structure that shunts blood from the pulmonary artery to the aorta by bypassing the nonfunctional lung and normally closes soon after birth [56]. After birth, the rise in systemic pressure and the drop in pulmonary artery pressure cause blood to flow through the PDA from the aorta to the pulmonary artery (left-to-right shunt), resulting in pulmonary over circulation and volume overload of the left atrium and LV [56]. A study by Spalla et al compared dogs with PDA with healthy controls and found a significant increase in LV dimensions, indicating LV overload in the PDA groups (Table 3) [47].…”
Section: Patent Ductus Arteriosus (Pda)mentioning
confidence: 99%
“…Echocardiography has been used in veterinary medicine since the early 1980s as a non-invasive method for assessing cardiac anatomy and function, providing quantitative information during systole and diastole, and serving as a tool for calculating myocardial function (Boon, 2011;Corda et al, 2019;Dickson et al, 2017;Tilley & Goodwin, 2002). It also allows the evaluation of the relationship between the structure of the heart and blood flow through direct visualization of the cardiac chambers (Corda et al, 2019;Dickson et al, 2017;Gugjoo et al, 2014;Vurucu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Utilizing LV border tracking XStrain4D delivers a more complete and intuitive picture of cardiac deformation behavior, providing temporal compensation for heart rate variations, spatial alignment of the 3 views in 3D space, and adaptation of a dynamic LV surface model. This tool, relying on the high spatial and temporal resolution of 2D imaging acquisitions, addresses and resolves the major limitations and criticalities currently related to the use of fullvolume 3D STE [10][11][12][13][14]. Moreover, this advanced technique can analyse both deformation and rotational parameters meticulously, thoroughly, and accurately.…”
Section: Introductionmentioning
confidence: 99%